Krisis Moralitas dalam Penegakan Hukum dan Relevansi Filsafat Hukum Pancasila Sebagai Solusi - Rubianti, Vaganti Safa Sukma (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Law enforcement in Indonesia frequently faces a moral crisis that results in an imbalance between positive law and the public's sense of justice. In this context, the Pancasila Legal Philosophy plays a fundamental role as an ethical basis and moral guideline in building a just national legal system. This study aims to analyze how the Pancasila Legal Philosophy explains the relationship between morality and law enforcement, and how the application of its values can provide a solution to the moral crisis in Indonesia. The research method used is normative legal research with a statute approach and a conceptual approach, as well as a review of literature and the views of legal experts, particularly Satjipto Rahardjo. The results show that Pancasila values, such as humanity, justice, and democracy, must be the foundation of every process of law enforcement and formation. The case of law enforcement irregularities in the Ferdy Sambo case and the discussion of the TNI Bill with minimal public participation reflect weak legal morality. Therefore, internalization of the values of Pancasila Legal Philosophy is necessary to realize laws that not only uphold certainty, but also guarantee justice and humanity.